Comments and illustrations of the WFUMB CEUS liver guidelines: Rare malignant hematological liver lesions - Zadeh, Ehsan Safai; Görg, Christian; Huber, Katharina Paulina; Dirks, Klaus; Jenssen, Christian; Lim, Adrian; Möller, Kathleen; Götzberger, Manuela; Dong, Yi; Cui, Xin Wu; Fetzer, David T.; Klinger, Christoph; et al. (Medical ultrasonography, 2024)
Diagnosing rare hematological malignancies in the liver is often challenging owing to their infrequency, and confirmation generally necessitates histological examination. Due to the rarity of these lesions, there are limited data concerning their appearance on ultrasound and, specifically, contrast-enhanced ultrasound. In this review, we describe the pathological and ultrasound features of several hematological malignant liver lesions, including lymphoma of the liver and chloroma. Furthermore, two specific forms of liver lymphoma are described: mucosa-associated lymphoid tissue (MALT) lymphoma andplasmacytoma of the liver.
Gesehen am 25.07.2025